Philosophy, framework and management tools to ensure a needs led approach to nonprofit/voluntary organization work - Bruce, Ian (Henry Stewart Talks, 2009)
Definitions of marketing, Why are nonprofits not automatically customer orientated?, Who are the customers?, Types of products, Rules of product composition, Eight points of charity marketing mix, Factors to consider when introducing a marketing approach to an organization, Basic nonprofit marketing/service plan